Defining and Inscribing 'Multicultural Library Services' in Australia: A Case Study of the Working Group on Multicultural Library Services (Victoria). Issue 1 (2nd January 2021) - Hegarty, Kieran
ABSTRACT: In this article, I survey efforts by librarians to alter collections and services amidst the demographic and political transformations of late twentieth century Australia. To examine this complex history, I focus on the Working Group on Multicultural Library Services (Victoria). For two decades, this independent group were active in positioning public libraries as key to the promotion and endorsement of a multicultural Australia. Using Group archives and interviews with key members, I argue that dominant understandings of recognising and accommodating cultural difference in libraries reflect the limitations of state multiculturalism. To demonstrate this, I focus on two Group activities: the state-wide adoption of the Standards for multicultural public library service, and lobbying by the Group for a national languages policy. While the former adopted the language of welfare provision based on discrete ethno-cultural groups, the latter echoed the emerging policy discourse of 'productive diversity'. In this case study, I critique the politics embedded in how 'cultural diversity' is typically understood within libraries and how library policies and practices are implicated in broader social and political developments. Such an approach offers insight into steady shifts in how the role of public libraries in culturally heterogenous societies have been debated and defined.